2014 IEEE International Conference on Communications (ICC) 2014
DOI: 10.1109/icc.2014.6883315
|View full text |Cite
|
Sign up to set email alerts
|

Joint mode selection, channel allocation and power assignment for green device-to-device communications

Abstract: Device-to-Device (D2D) communication has emerged as a promising technique for improving capacity and reducing power consumption in wireless networks. Most existing works on D2D communications either targeted CDMA-based singlechannel networks or aimed to maximize network throughput. In this paper, we, however, aim at enabling green D2D communications in OFDMA-based wireless networks. We formally define an optimization problem based on a practical link data rate model, whose objective is to minimize power consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 12 publications
0
49
0
Order By: Relevance
“…User-2 can estimate the channel gain of the D2D link by detecting the D2D beacon transmitted by user-1, and report this information to the BS. The BS then solves the mode selection problem (verifying conditions (10) or (11), depending on the desired energy consumption to minimize), and broadcasts the decision together with the allocated resources to the mobile users.…”
Section: Implementation Guidelinementioning
confidence: 99%
See 1 more Smart Citation
“…User-2 can estimate the channel gain of the D2D link by detecting the D2D beacon transmitted by user-1, and report this information to the BS. The BS then solves the mode selection problem (verifying conditions (10) or (11), depending on the desired energy consumption to minimize), and broadcasts the decision together with the allocated resources to the mobile users.…”
Section: Implementation Guidelinementioning
confidence: 99%
“…In [9], the authors address the mode selection problem of a single pair of mobile users with two dual performance objectives: to maximize the quality-of-service (QoS) for a given transmit power, and to minimize the power for a given QoS. The latter formulation has later been extended to the multiple link case in OFDMA-based networks [10], but the multi-link formulation has high computational complexity and was solved using heuristic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…It has been recently shown that there are more than four million base stations (BSs) each consuming an average of 2.3MWh per month [2], and the volume of newly deployed BSs is growing exponentially, especially in the developing counties. Such an extreme energy consumption burden has its influence on the energy costs, greenhouse effect, and global impact on climate in general [3].…”
Section: Introductionmentioning
confidence: 99%
“…Since we have ensured power feasibility only for communications in cellular mode, we need to verify that r max ll T ≤ b l before applying (13). It turns out to be more convenient to work with the extended value function…”
Section: ) Minimum Energy Cost For Communication In Cellular Modementioning
confidence: 99%
“…Several works have investigated this joint problem [8]- [10], mainly developing mixed-integer programming models and dealing with NP-hard formulations. Hence, heuristics [11]- [13] and game-theoretic approaches [14] have also been explored as more practical alternatives.…”
Section: Arxiv:150600412v1 [Csit] 1 Jun 2015mentioning
confidence: 99%